Midline Approach to Pediatric Nasofrontal Dermoids. (23rd August 2013) - Ortlip, Timothy; Ambro, Bryan T.; Pereira, Kevin D.
Abstract : Objectives: Highlight the surgical approaches and cosmetic considerations involved in the management of pediatric nasofrontal dermoid cysts. We reviewed the various surgical approaches in comparison to our own experience using the vertical midline incision. Methods: Case series of 4 different types of nasal dermoids, including 1 with an intracranial extension managed at a single tertiary medical center over a 2 year period. Results: There were a total of 4 patients. The mean age at surgery was 2.5 years. The anatomic location of the nasal dermoids differed in each patient: 1) supratip, 2)upper dorsum, 3)tip and supra‐tip, 4)tip and upper dorsum. Computed tomography and magnetic resonance imaging was performed on all patients. There was one case of intracranial extension. All 4 patients underwent surgical removal of the lesions with excision of involved skin using the vertical midline incision. Nasal reconstruction was performed with local soft tissue flaps (1 patient), Alloderm® (2 patients), and bone dust pate (1 patient). The patient with intracranial involvement also underwent a frontal craniotomy to excise the intracranial component. All 4 lesions were histologically confirmed as dermoid cysts. Mean follow‐up was 1.5 years. There were no complications or recurrences. All patients had a cosmetically acceptable incisional scar. Conclusions: A vertical midline incision with modifications to excise involved skin provides a satisfactory and cosmetically sound approach to congenital lesions of the nasofrontal region. It affords adequate exposure for excision and reconstruction. A multi‐disciplinary team consisting of neurosurgery, facial plastics, and pediatric otolaryngology are needed to optimize outcomes.